(untitled) (CIPEEX, 2022)
TATTOOING IS AN ACT OF BODY EXPRESSION AND SOCIAL COMMUNICATION WITH GREAT POPULARITY BECAUSE IT WORKS AS AN INDIVIDUAL SUBJECTIVATION. FOR BEING AN INVASIVE PROCEDURE, WHICH BREAKS THE EPITHELIAL BARRIER, IT ACTS AS A POTENTIAL SOURCE OF INFECTION AND CONTAMINATION. THE INK IS ONE OF THE PROTAGONISTS FOR THIS TO OCCUR. OBJECTIVE: THE OBJECTIVE OF THIS WORK IS TO CARRY OUT MICROBIOLOGY OF INKS USED IN TATTOO STUDIOS IN AN EVALUATION IN AN INTERIOR CITY OF GOIS. METODOLOGY: IT IS AN OBSERVATIONAL, DESCRIPTIVE, AND QUANTITATIVE ORIGINAL STUDY, WITH A SAMPLE OF TEN STUDIOS AMONG WHICH ONLY SEVEN HAVE DONATED MATERIAL FOR ANALYSIS. ALL PARTICIPANTS ANSWERED A QUESTIONNAIRE WITH TWENTY OBJECTIVE QUESTIONS ABOUT THE PROCEDURES CARRIED OUT IN THE STUDIOS. IRREGULARITIES SUCH AS THE INCOMPLETE USE OF INDIVIDUAL PROTECTION EQUIPMENT, IMPROPER STORAGE OF ITEMS, AND REUSE OF MATERIAL THAT SHOULD DISCARDED HAVE BEEN VERIFIED. 5 ML OF PURE INK AND 5 ML OF INK AND DILUENTS WERE SEEDED IN SELECTIVE MEDIUM MANNITOL AGAR AND AGAR MAC CONKEY. RESULTS: THERE WAS BACTERIAL GROWTH PRESENT IN BOTH MEDIUM QUANTIFIED ABOVE 25X104 CFU/ML IN 5 SAMPLES AND 0,3X104 CFU/ML IN JUST ONE SAMPLE IN THREE OF THE SEVEN ANALYZED STUDIOS. THIS CONFIRMS CONTAMINATION OF INK BY GRAM POSITIVE AND NEGATIVE BACTERIA. LACK OF INSPECTION, INADEQUATE USE OF INDIVIDUAL PROTECTION EQUIPMENT, FAILURES IN HYGIENE PROTOCOLS, REUSE OF MATERIALS THAT SHOULD BE DISCARDED, AND THE INAPPROPRIATE USE OF DILUENTS ARE FACTORS THAT MAY BE RELATED TO THIS CONTAMINATION. CONCLUSION: THERE IS A NEED FOR FURTHER STUDIES OF THIS NATURE DUE TO THE GROWING DEMAND FOR THIS ART FORM, FOR THE INTRINSIC RISK ASSOCIATED WITH IT, AND FOR BETTER SUPERVISION AND GUIDANCE OF PROFESSIONALS TO STRICTLY FOLLOW THE HYGIENE PROTOCOLS.